Bottom-up model for understanding the effects of wheat endosperm microstructure on its mechanical strength. (December 2016) - Chichti, Emna; Lullien-Pellerin, Valérie; George, Matthieu; Radjai, Farhang; Affès, Rafik; Delenne, Jean-Yves
Abstract: Wheat flours are essential ingredients of daily food products like bread, cookies or pastries. Their quality depends on the milling process and mechanical strength of wheat grains. Although it is well known that the strength and rupture of grains are strongly controlled by the endosperm microstructure, the respective roles of the starch and polymer volume fractions and their adhesion are not yet fully understood. This typical biological microstructure can be modeled as a cemented granular material, where the two size populations of starch granules (large:A-type, small:B-type) are the particles, and the protein matrix, which partially fills the space between granules, plays the role of a cement. This structural model of wheat endosperm is used, together with mechanical characteristics of starch and proteins obtained by means of Atomic Force Microscopy (AFM) measurements, to simulate the mechanical behavior and breakage of wheat endosperm in milling process. We find that the porosity outweighs the effect of other parameters for the elastic modulus, which declines as a nearly linear function of porosity. We also show that the tensile strength is an increasing function of the amount and connectivity of starch granules with increasing concentration of stresses along chains of granules. This effect is more significant at low porosity where stress distribution is mainly controlled by the contact network between starch granules. This effect explains why the protein content is not fully correlated to vitreousness, and samples of similar protein content can be different in vitreosity. Finally, we find that the starch-granule adhesion strongly affects the tensile strength whereas the effect of starch volume fraction appears mainly at high interface adhesion, which is the case of hard type wheat grains. Highlights: A numerical model of the mechanical behavior of wheat endosperm based on micro-structural parameters. A detailed analysis of the effect of starch, protein matrix and porosity content on the strength and failure. A clarification of the role of starch granule volume fraction and connectivity for the tensile strength of wheat endosperm. A physical interpretation of wheat textural properties such as hardness and vitreousness.